Synthesis and Electroluminescence Studies of CdSe Nanocrystals Embedded in PVK Matrix - Kumari, Sarita; Dubey, Swati; Ramrakhiani, Meera (International Journal of Computer Sciences and Engineering, 2025)
There is currently a great interest in semiconductor nanoparticles which are organically capped or embedded in polymeric matrices for their ready to use application in devices. These materials show excellent optical and mechanical behaviour at Nano scale. Nano crystalline powder and nanocomposites of II-VI compounds with different doping are being prepared by various routes. Poly-vinylcarbozole (PVK) is a hole transport organic semiconducting polymer. It has been widely used as an organic and optical material. Combination of polymer and semiconductor nanocrystals allows the fabrication of flexible and light weight EL devices. Electroluminescence of the films was studied at different voltage and frequency by placing the films between ITO coated conducting glass plate and aluminium electrodes. It is found that a turn on voltage is required for light emission and brightness increases exponentially with voltage. Turn on voltage is found to decrease as CdSe concentration is increased.